Nature-Inspired Total Synthesis of (−)-Fusarisetin A - Xu, Jing (2012)
A concise, protecting group-free total synthesis of (−)-fusarisetin A (1) was efficiently achieved in 9 steps from commercially available (S)-(−)-citronellal. The synthetic approach was inspired by our proposed biosynthesis of 1. Key transformations of our strategy include a facile construction of the decalin moiety that sets the stage for a stereoselective IMDA reaction and a one-pot TEMPO induced radical cyclization/aminolysis that forms the C ring of 1. Our route is amenable to analogue synthesis for biological evaluation.